PERTUMBUHAN DAN HASIL KEDELAI EDAMAME DENGAN PEMBERIAN KOMBINASI PUPUK KANDANG AYAM DAN NPK YANG DIPERKAYA MIKROBA FUNGSIONAL PADA TANAH ALUVIAL - Irpansyah, Irpansyah; Palupi, Tantri (Fakultas Pertanian, Universitas Janabadra, 2024)
Edamame soybean (Glycine max L.) is a food crop that has great potential for cultivation in West Kalimantan. Increasing the production of edamame soybeans is necessary considering the high demand for soybeans in Indonesia every year. Efforts to increase production can be carried out on aluvial soil by providing a combination of chicken manure and NPK enriched with PGPR functional microbes. This study aimed to determine the effect and obtain the best dose of a combination of chicken manure and NPK enriched with functional microbes on the growth and yield of edamame soybeans in aluvial soil. The design used in this study was a completely randomized non-factorial design, with 5 treatments, each treatment 5 replications, each replication consisting of 4 plant samples. The treatment consisted of p1 = 15 tonnes/ha of chicken manure + PGPR, p2 = 11.25 tonnes/ha of chicken manure + 50 kg/ha of NPK + PGPR, P3 = 7.5 tonnes/ha of chicken manure + 100 kh /ha NPK + PGPR, p4 = 3.75 tonnes/ha of chicken manure + 150 kg/ha NPK + PGPR, p5 = 200 kg/ha NPK (control). Observational variables included plant height (cm), root volume (cm3), crown dry weight (grams), root dry weight (g), number of productive branches (branches), number of pods (pods), pod weight (g), number of seeds /pods (seeds), root length (cm) and number of root nodules (nodules). The results showed that the combination of chicken manure and NPK enriched with functional microbes had no significant effect on all growth and yield variables of edamame soybeans. Key-words: chicken manure, edamame soybeans, PGPR, NPK, aluvial soil